Productivity, Efficiency, and Economic Growth in the Asia-Pacific Region - Lee, Jeong-Dong.; Heshmati, Almas. (Contributions to Economics,, 2009)
Productivity growth is a keyword for sustainable economic growth in a knowledge-based society. There has been significant methodological development in the literature on productivity and efficiency analysis, e.g. SFA (Stochastic Frontier Analysis) and DEA (Data Envelopment Analysis). All these methodological developments should be matched with applications in order to provide practical implications for private and public decision-makers. This volume provides a collection of up-to-date and new applications of productivity and efficiency analysis. In particular, the case studies cover various economic issues in the Asia-Pacific region. The authors analyze the performance of manufacturing firms, banks, venture capital, broadcasting firms, as well as the issues of efficiency in the education sector, regional development, and defense industry. These case studies will shed light on the potential contribution of productivity and efficiency analysis to the enhancement of economic performance.